Sustainability assessment of rice production systems in Mazandaran Province, Iran with emergy analysis and fuzzy logic. (August 2020) - Amini, Sherwin; Rohani, Abbas; Aghkhani, Mohammad Hossein; Abbaspour-Fard, Mohammad Hossein; Asgharipour, Mohammad Reza
Highlights: Proper use of chemical fertilizers increases the sustainability of products. Reducing nonrenewable inputs makes agroecosystems more sustainable. Energy efficiency can be improved by optimizing the inputs of the appropriate model. Upright management of economic and agronomic factors can improve sustainability. More care should be taken for fertilizer and fuel consumption of Paddy fields. Abstract: The analysis of energy consumption patterns in agriculture is vital because of the concern for natural resources and the adverse effects of the misuse of various energy resources on human and environmental health. The present research is an attempt on the ecological sustainability assessment of rice production in Mazandaran Province, Iran, using the emergy analysis approach and fuzzy logic. Two agricultural and economic models were used to study sustainability, using the fuzzy logic. Our assessment of rice production showed that if economic indices and the ultimate production index are used instead of agricultural factors, higher production sustainability is achieved. The total estimated emergy used for rice production was 5.34E + 16sej ha −1 . Renewable and nonrenewable environmental resources accounted for 8.28% and 91.72% of the total emergy, respectively. The resulting standard environmental loading ratio (43.87) and the modified environmental loading ratio (11.11) were also larger than the average values reported in similar studies elsewhere. This implies a relatively heavy pressure exerted by these crop systems on the environment. In the current study, the environmental sustainability index (0.12) and its modified version (0.46) were smaller than the average values obtained in previous studies, showing a lower average sustainability of this system. Hence, given the average sustainability and the heavy environmental load of this system, a model suiting the region can be developed, to improve energy efficiency by optimizing the labor and consuming potassium fertilizers and fuels. Finally, it is recommended that rice production in this temperate region should be performed more carefully and cautiously, especially in relation to the use of chemical fertilizers and fuels.